Targeting HER2 alterations in non-small cell lung cancer: Therapeutic breakthrough and challenges. (March 2023) - Yu, Ying; Yang, Yehao; Li, Hui; Fan, Yun
Highlights: T -DXd has achieved a significant breakthrough and has been approved by the FDA for pretreated advanced HER2-mutant NSCLC. Although poziotinib has shown promising antitumour activity, the significant toxicity hinders its subsequent development. An explicit definition of the cut-off values for HER2 amplification or overexpression is imperative. Future studies should focus on T -DXd-based therapy and the intracranial activity of anti-HER2 agents. Abstract: In non-small cell lung cancer (NSCLC) with human epidermal growth factor receptor 2 (HER2) alterations, chemotherapy remains the standard treatment over a decade, due to the minor efficacy of traditional pan-HER tyrosine kinase inhibitors (TKIs) and HER2-targeted monoclonal antibodies. In recent years, novel selective HER2 TKIs have been developed for pretreated HER2-mutant patients. In particular, pyrotinib has shown moderate efficacy as well as a manageable safety profile, and it is now being further evaluated as monotherapy or combined with other existing therapies; by contrast, while poziotinib has demonstrated promising preliminary results, the high rates of toxicity has hampered subsequent studies. Most notably, trastuzumab deruxtecan ( T -DXd, DS-8201) has led to a significant breakthrough, with the most encouraging efficacy data (response rate of 55 %, median progression-free survival of 8.2 months and median overall survival of 17.8 months) among all the anti-HER2 agents. This is certainly remarkable progress, and T -DXd is undoubtedly the key drug for the treatment of this disease. Future developments regarding T -DXd are favourable, including shifting from monotherapy to combination strategies, improving structural design to optimise antitumour activity and minimise toxicity, identifying the potential resistance mechanisms and developing therapeutic strategies to overcome them. Several other challenges need to be addressed, such as the intracranial activity of anti-HER2 agents and the optimal sequencing of therapies. Here, we summarise recent therapeutic advances in targeting HER2 alterations in NSCLC and highlight the future perspectives of these patient populations.